2014
DOI: 10.5851/kosfa.2014.34.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hempseed (Cannabis sativa sp.) Inclusion to the Diet on Performance, Carcass and Antioxidative Activity in Japanese Quail (Coturnix coturnix japonica)

Abstract: This study was conducted to determine the effects of hempseed (H) on performance, carcass traits, and antioxidant activity in Japanese quail (Coturnix coturnix japonica). A total of 192 quail with seven-days old were divided into four experimental groups with four replicates. The treatments were; i) Control diet (C, no hempseed); ii) 5% hempseed in diet (H5); iii) 10% hempseed in diet (H10); and iv) 20% hempseed in diet (H20). The body weight (BW) and feed intake (FI) of quail was determined at 7, 21 and 42 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
5
14
0
Order By: Relevance
“…Present results were in agreement reported by Ismail, Al‐Naqeep, and Chan () and Talha, Priyanka, and Akanksha () in chicken and Konca, Cimen, Yalcin, Kaliber, and Beyzi () in Japanese quails. Feeding of aqueous extract of dill seed in rats produced similar effects (Bano, Ikram, & Akhtar, ).…”
Section: Discussionsupporting
confidence: 93%
“…Present results were in agreement reported by Ismail, Al‐Naqeep, and Chan () and Talha, Priyanka, and Akanksha () in chicken and Konca, Cimen, Yalcin, Kaliber, and Beyzi () in Japanese quails. Feeding of aqueous extract of dill seed in rats produced similar effects (Bano, Ikram, & Akhtar, ).…”
Section: Discussionsupporting
confidence: 93%
“…Superoxide dismutase activity was highest at a concentration of 1000 μg/mL and reached up to 178% and 165% for UAE and MAE extract, respectively. The ability of chemical compounds contained in cannabis extracts to increase SOD activity has also been confirmed by other authors, including in vivo studies [ 36 , 37 ]. Antioxidant abilities of plant extracts, including Cannabis sativa L. extract, are extremely important because they allow cells to be protected against oxidative stress, lipid peroxidation or DNA damage.…”
Section: Resultssupporting
confidence: 63%
“…The results obtained in this study are somewhat confirmed by Hu et al (2008), who reported that serum MDA concentration was decreased in rats fed on diets with hemp seed oil compared with control groups fed on diets containing soybean oil. Additionally, Konca et al (2014), reported a decrease in the liver MDA concentration in laying Japanese quail, suggesting hemp seed has potential as a natural antioxidant.…”
Section: Resultsmentioning
confidence: 98%
“…Currently, there has been not enough research into the effects of hemp inclusion in animal diets and its nutritive and antioxidant efficacy in animals (Konca et al, 2014). Consequently, the current study was designed to assess the effect dietary intake of hemp seeds or cake on milk production and the FA profile of milk.…”
Section: Introductionmentioning
confidence: 99%